A PENERAPAN BLENDED LEARNING BERBASIS WEB COURSE UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA KELAS VIII PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Priza Tri setya Wicaksana (Program Studi S1 Matematika UNESA, 2021)
In today's millenial era, people should be able to learn anywhere and anytime. In fact, what is meant is to study group or learn individually. But the reality in the field shows that the learning used still applies traditional learning, namely classroom-based learning with teachers as information centers. Teachers are also asked to be able to adapt to current conditions by combining learning with the progress of communication and information technology that is developing today. Learning models, media, and attitudes that support the above statements are blended learning, google classroom application media, and high self-reliance owned by students. The purpose of this research is to improve the learning independence skills of learners through the application of blended learning models. The research instruments used are observation sheets of blended learning methods, observation sheets of student activities, self-reliance questionnaires and student response questionnaires. Data retrieval techniques in this study using observation methods, tests and questionnaires. Based on data analysis obtained on learning devices, normalized gain calculation, quality of blended learning method implementation, and student response questionnaires get excellent results. In the calculation of normalized gain calculations get a score of 0.794 from these results, the independence of students' learning belongs to a high category. From these results, it can be concluded that students are very interested in blended learning methods that have been applied so as to increase the independence of learning of grade VIII students in the two-variable Linear Equation System material.